Spatially resolved photocatalytic active sites and quantum efficiency in a 2D semiconductor - Olivier Henrotte; Seryio Saris; Franz Gröbmeyer; Christoph G. Gruber; Ismail Bilgin; Alexander Högele; Naomi J. Halas; Peter Nordlander; Emiliano Cortés; Alberto Naldoni (Nature Communications)
Abstract Identifying reactive sites and measuring their activities is crucial for enhancing the efficiency of every catalyst. Reactivity maps can guide the development of next-generation photocatalysts like 2D transition metal dichalcogenides, which suffer from low conversion rates. While their electrocatalytic sites are well-studied, their photocatalytic sites remain poorly understood. Using scanning photoelectrochemical microscopy, we spatially resolve the photoreactivity of MoS2 monolayers, a prototypical 2D transition metal dichalcogenide, for redox reactions, including H2 production from water. Aligned-unaligned excitation-detection measurements reveal that photogenerated holes and electrons exhibit distinct behaviors. Oxidation products localize at the excitation spot, indicating stationary holes, while photoreduction occurs up to at least 80 microns away, showing exceptional electron mobility. We also elucidate the photochemical reactivity according to the nature of the electronic excitation, showing that the internal quantum efficiency of strongly-bound A-excitons outperforms weakly-bound (free-carrier like) C-excitons across the flake. These findings offer novel guidance to rationally design 2D photocatalysts via engineering their optical and charge extraction abilities for efficient solar energy conversion.